FISIOLOGIA REPRODUTIVA EM ÉGUAS – BREVE REVISÃO - da Silva, Tais Lopes; Batiston, Nicoli; Alves, Bruna Farias; Travi, Magdalena Reschke Lajús; Carneiro, Maico Fernando Wilges; Danelus, Marina Oliveira (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.